Influence of Fano resonance on SERS enhancement in Fano-plasmonic oligomers - Dutta, Arpan; Alam, Khairul; Nuutinen, Tarmo; Hulkko, Eero; Karvinen, Petri; Kuittinen, Markku; Toppari, J. Jussi; Vartiainen, Erik M. (Optics express, 2019)
Plasmonic oligomers can provide profound Fano resonance in their scattering responses. The sub-radiant mode of Fano resonance can result in significant near-field enhancement due to its light trapping capability into the so-called hotspots. Appearance of these highly localized hotspots at the excitation and/or Stokes wavelengths of the analytes makes such oligomers promising SERS active substrates. In this work, we numerically and experimentally investigate optical properties of two disk-type gold oligomers, which have different strength and origin of Fano resonance. Raman analysis of rhodamine 6G and adenine with the presence of the fabricated oligomers clearly indicates that an increment in the strength of Fano resonance can improve the Raman enhancement of an oligomer significantly. Therefore, by suitable engineering of Fano lineshape, one can achieve efficient SERS active substrates with spatially localized hotspots.Plasmonic oligomers can provide profound Fano resonance in their scattering responses. The sub-radiant mode of Fano resonance can result in significant near-field enhancement due to its light trapping capability into the so-called hotspots. Appearance of these highly localized hotspots at the excitation and/or Stokes wavelengths of the analytes makes such oligomers promising SERS active substrates. In this work, we numerically and experimentally investigate optical properties of two disk-type gold oligomers, which have different strength and origin of Fano resonance. Raman analysis of rhodamine 6G and adenine with the presence of the fabricated oligomers clearly indicates that an increment in the strength of Fano resonance can improve the Raman enhancement of an oligomer significantly. Therefore, by suitable engineering of Fano lineshape, one can achieve efficient SERS active substrates with spatially localized hotspots.